2018
DOI: 10.2174/1389201019666180808165309
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Intracellular Ca2+ Signals to Stimulate Therapeutic Angiogenesis in Cardiovascular Disorders

Abstract: Endothelial progenitor cells (EPCs) are mobilized in peripheral blood to rescue blood perfusion in ischemic tissues. Several approaches were, therefore, designed to inject autologous EPCs and induce therapeutic angiogenesis in patients affected by cardiovascular disorders. Endothelial colony forming cells (ECFCs) represent the only truly endothelial precursor and are regarded as the most suitable substrate for cell based therapy of ischemic diseases. Intracellular Ca2+ signalling drives ECFC proliferation, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…This landmark discovery fostered an intense search for the most effective strategy to utilize EPCs for the regenerative therapy of ischemic disorders. However, the therapeutic use of EPCs has been hampered by inconsistent definitions and different protocols employed to isolate and expand them from peripheral and umbilical cord blood [ 15 , 16 , 17 ]. It has been demonstrated that two distinct and well-defined EPC subtypes may emerge from cultured mononuclear cells, which differ in their ontology and reparative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This landmark discovery fostered an intense search for the most effective strategy to utilize EPCs for the regenerative therapy of ischemic disorders. However, the therapeutic use of EPCs has been hampered by inconsistent definitions and different protocols employed to isolate and expand them from peripheral and umbilical cord blood [ 15 , 16 , 17 ]. It has been demonstrated that two distinct and well-defined EPC subtypes may emerge from cultured mononuclear cells, which differ in their ontology and reparative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, TRPV4-mediated extracellular Ca 2+ entry supported AA-evoked intracellular Ca 2+ signals, NO release and PB-ECFC proliferation (Dragoni et al, 2015a). This feature could become therapeutically relevant as AA is massively released in circulation during myocardial ischemia and upon brain damage (Moccia et al, 2018a). Unlike TRPV4, TRPV1 activation is per se sufficient to induce ECFC proliferation.…”
Section: The Role Of Trpv1 and Trpv4 In Vasculogenesismentioning
confidence: 98%
“…Genetic (with specific siRNAs) and pharmacological (with Pyr3) manipulation revealed that TRPC3-mediated extracellular Ca 2+ entry triggers the dynamic interplay between InsP 3 Rs and SOCE which shapes the spiking Ca 2+ response to VEGF, thereby promoting UCB-ECFC proliferation (Dragoni et al, 2013). It has been suggested that TRPC3 involvement is responsible for the higher frequency of VEGF-induced intracellular Ca 2+ oscillations in UCB-ECFCs, which is associated to their higher proliferative potential (Moccia et al, 2018a). This observation led to the hypothesis that the exogenous insertion of TRPC3 might rejuvenate the reparative phenotype of senescent/aging UCB-ECFCs, thereby improving the efficacy of autologous cell-based therapy in ischemic patients (Moccia et al, 2018a).…”
Section: The Role Of Trpc1 and Trpc3 In Vasculogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of Ca 2+ from the endoplasmic reticulum leads to the accumulation of stromal interaction molecule 1 protein in the endoplasmic reticulum membrane, which eventually evokes Ca 2+ in ux by activating Orai channels located in the cell membrane [13]. SOCE participates in various physiological and pathological activities, such as cell proliferation and migration regulation, immune response, and cancer development [14][15][16]. However, the regulatory effect of SOCE in human lens epithelial cells has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%